Pengolahan Air Sumur Bor Menjadi Air Bersih Menggunakan Proses Koagulasi-Filtrasi - Anggun, Anggun Rasmini; Sanjaya, Rendy Eka; Kadaria, Ulli; Asbanu, Govira Christiadora (Al-Ard: Jurnal Teknik Lingkungan, 2024)
The community's need for clean water is a complex matter in meeting needs such as washing, cooking, bathing and other needs, so the quality and quantity need to be maintained. The Jalan Parit Wagattak area still uses drilled well water to fulfill daily needs because there is no distribution route from PDAM. The quality of iron (Fe) parameters at the research location does not meet the quality standards, namely still 1.52 mg/L. This research aims to make the drilled well water used suitable by processing it using a coagulation-filtration process. The optimum dose of chlorine obtained from the Jar Test results was 5 mg/L with a maximum stirring time of 30 minutes. The zeolite filter media used has a height of 20 cm with a PVC pipe container diameter of 3 inches. The results of the allowance for turbidity parameters from 221 NTU to 12.67 NTU (94.26%), color from 32.9 Pt-Co to <1.45 Pt-Co (95.59%), iron (Fe) 1.52 mg/L decreased to 0.04 mg/L (97.36%), Escherichia coli 16 MPN/ml to 0.89 MPN/ml (94.43%), pH increased from 6.4 to 7.2, and the remaining free chlorine (Cl2) from 0.03 mg/L to 0.04 mg/L. Based on the research carried out, it is necessary to determine the contact time between water and zeolite to eliminate turbidity and Escherichia coli happens to the maximum.